Results of Virus Isolation and Serology testing on Influenza A Virus Samples from Lesser Scaup (Aythya affinis) and Greater Scaup (Aythya Marila) ... - Harrison Huang; Rebecca L. Poulson; Jeffery D Sullivan; Susan E De La Cruz; Hutchison Walbridge; David E Stallknecht; Diann J Prosser (U.S. Geological Survey, 2024)
These data describe the results of virus isolation from oropharyngeal/cloacal swabs and testing of sera by a commercial blocking enzyme-linked immunosorbent assay (bELISA) and hemagglutinin (HA) specific testing by microneutralization (MN) and hemagglutination inhibition (HI) for Lesser Scaup in both the Atlantic and Pacific Flyways and Greater Scaup in the Pacific Flyway. These data support a USGS published manuscript. ...